Genomics-based drug innovation: visions and commercial viability. (20th November 2008) - Kraft, Alison; Rothman, Harry
This paper tracks the development of genomics between 1990 and 2005 principally within the US context and reviews that development with specific respect to early expectations of genomics-based pharmaceutical innovation, the initial claims made for it, and the realities of its current position. Emphasis is placed on relations between the genomics sector and its larger pharmaceutical and biotechnology counterparts, and to the financial markets on which drug innovation ultimately rests. The analysis combines historical and sociological approaches to the study of innovation, and situates genomics within the wider context of the commercialisation of the life sciences. In particular, we highlight and reflect critically on the disparity between the expectations and 'hype' surrounding genomics, and assess its impact, to date, on pharmaceutical innovation.